The role of prehabilitation with a telerehabilitation system prior to total knee arthroplasty - Chughtai, Morad; Shah, Neil V.; Sultan, Assem A.; Solow, Maximillian; Tiberi, John V.; Mehran, Nima; North, Trevor; Moskal, Joseph T.; Newman, Jared M.; Samuel, Linsen T.; Bhave, Anil; Mont, Michael A. (Annals of Translational Medicine, 2018)
Background: The purpose of the current study was to evaluate the usage of prehabilitation on a telehealth platform prior to total knee arthroplasty (TKA) and its impact on short-term outcomes. Specifically, the study examined whether patients participating in a prehabilitation program impacted length of stay (LOS) and discharge disposition. Methods: A total of 476 consecutive patients who underwent TKA at three institutions were included. The average age of the 476 patients was 65.1 years (range, 35 and 93 years). There was a total of 114 patients who utilized the novel prehabilitation program that provided exercises, nutritional advice, education regarding home safety and reducing medical risks, and pain management skills prior to surgery. A group of 362 patients who did not utilize the program formed the control cohort. The outcomes evaluated were LOS and discharge disposition to home, home with health aide (HHA), or skilled nursing facility (SNF). Results: The average LOS in the prehabilitation group was significantly shorter than in the control group (2.0 vs. 2.7 days, P